¿Senderos divergentes y resultados convergentes? La desigualdad económica en Europa y América Latina en las primeras décadas del siglo XXI - Salvia, Agustín; Poy, Santiago; Lamarmora, Guido (El Colegio de México A.C., 2020)
The article analyzes the changes in intra- and inter-regional economic inequality in Latin America and Europe. Taking a sample of 44 countries, it examines the extent to which economic and productive factors together with welfare policies bring about structural differences in terms of inequality between and within regions over the period 2000-2017. The results reveal that the inter-regional inequality gap was reduced as a result of different intra-regional dynamics: inequality fell in most Latin American countries while it rose in European countries. The analysis of national trajectories shows that this was due to simultaneous changes in the style of growth and in the redistributive efficiency of social spending.